Lysine specific demethylase 1 is a molecular driver and therapeutic target in sarcoma - Dreher, Rachel D.; Theisen, Emily R. (Frontiers in Oncology, 2023)
Sarcomas are a diverse group of tumors with numerous oncogenic drivers, and display varied clinical behaviors and prognoses. This complexity makes diagnosis and the development of new and effective treatments challenging. An incomplete understanding of both cell of origin and the biological drivers of sarcomas complicates efforts to develop clinically relevant model systems and find new molecular targets. Notably, the histone lysine specific demethylase 1 (LSD1) is overexpressed in a number of different sarcomas and is a potential therapeutic target in these malignancies. With the ability to modify histone marks, LSD1 is a key player in many protein complexes that epigenetically regulate gene expression. It is a largely context dependent enzyme, having vastly different and often opposing roles depending on the cellular environment and which interaction partners are involved. LSD1 has been implicated in the development of many different types of cancer, but its role in bone and soft tissue sarcomas remains poorly understood. In this review, we compiled what is known about the LSD1 function in various sarcomas, to determine where knowledge is lacking and to find what theme emerge to characterize how LSD1 is a key molecular driver in bone and soft tissue sarcoma. We further discuss the current clinical landscape for the development of LSD1 inhibitors and where sarcomas have been included in early clinical trials.